The relationship between anxiety and depression under the pandemic: The role of life meaning - Shek, Daniel T. L.; Chai, Wenyu; Tan, Lindan (Frontiers in Psychology, 2022)
COVID-19 is a stressor creating much anxiety for the general public, such as anxiety related to possible infection, social distancing, financial strain and uncertainty. As the scientific literature shows that there is an intimate relationship between anxiety and depression, it is important to ask whether anxiety is related to depression under the pandemic and whether spirituality indexed by life meaning can moderate the relationship between anxiety and depression. According to theories highlighting the importance of life meaning, relative to people with a higher level of life meaning, the relationship between anxiety and depression would be stronger in people with a lower level of life meaning. Empirically, we collected data in two waves (i.e., before and after the first wave of COVID-19, respectively) from 4,981 adolescents recruited in Sichuan, China. Then, the 41-item “Screen for Child Anxiety Related Emotional Disorders” was employed to measure anxiety symptoms, 20-item “Center for Epidemiological Studies-Depression Scale (CES-D)” was utilized to examine depression symptoms, and the “Spirituality Subscale of the Chinese Positive Youth Development Scale” for assessing life meaning. We found that anxiety significantly predicted depression at each wave and across time. Second, controlling for Wave 1 depression scores, results showed that a drop in Wave 1 anxiety predicted a drop in depressive symptoms over time. Regarding the relationship between meaning in life and depression, spirituality indexed by meaning in life negatively predicted depression at each wave and over time, and predicted change in depression across time. Finally, multiple regression analyses showed that life meaning moderated the predictive effect of anxiety on depression. The findings support the thesis that spirituality serves as a protective factor for psychological morbidity in Chinese adolescents. The study also suggests the importance of helping adolescents to develop life meaning under COVID-19.